THE EFFECT OF DIFFERENT SMOKING TEMPERATURE ON THE QUALITY OF SKIPJACK (Katsuwonuspelamis) KATSUOBUSHI - Ramadhana, Febriano; Leksono, Tjipto; Mus, Sukirno (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study aimed to observe the effect of different smoking temperature on the quality of skipjack (Katsuwonuspelamis) katsuobushi and to determine the best smoking temperature. The method used was an experimental and composed as non-factorial randomized complete design (RCD). The smoking temperature was differentiated into 3 levels of treatment, namely: of 40-50o C, 65-75o C and 90-100o C. The parameters used to assess the quality of katsuobushi produced were organoleptic test, water content, ash content, pH value, total plate count of microbia and fungal identification. The results showed that the best smoking temperature to produce the highest quality of skipjack katsuobushi was 90-100o C. It was shown by the highest value of appearance at 7.7 characterized by quite clean, slightly shiny without cracks, odor value at 7.8 characterized by specific wood fish odor reduced without additional odor, texture value at 7.4 characterized by hard and not easily broken, and taste value at 7.9 characterized by tasty and less tasty. The best katsuobushi contained of water 14.9%, ash 7.8%, pH value 5.4, phenol content 0.02 ppm, and TPC of bacteria 2.5 x 103 Cfu/g sample. The type of fungus grown on the skipjack tuna katsuobushi was Aspergillus sp.Keywords : katsuobushi, skipjack, smoking, temperature